Incidence of Vertigo distribution among young adult and elderly in patients attending Al-Diwaniya Teaching Hospital . Al-Diwaniya. - Yousef, Raid Yaqoub; humady, Ahmed (AL-Kindy College Medical Journal, 2013)
This study is prospective in nature, It consider110 patients with vertigo who were assessedbetween April and December 2010 at E.N.T outpatient department of otolarygiology, in AlDiwania teaching hospital, in Diwania city,Iraq. The study is designed to assess theincidence of vestibular and non vestibularvertigo and their association withtinnitus,hearing loss,migraine in Young adultand elderly.All patients were assessed byquestionary method and by pure toneAudiometry.Results: the incidence of vestibular vertigo was69.1% while non vestibular vertigo is 30.9 %,vestibular vertigo was inversely related to theage while non vestibular vertigo directly relatedto the ageThe percentage of association betweentinnitus, migraine, hearing loss withvestibular and non vestibular vertigo were{71%,6%),(29%,35%),(74%,18%)}correspondingly.Conclusion; vestibular vertigo was morecommon than non vestibular vertigo in youngadult and elderly, and it is significantlyassociated with tinnituswith migraine.